Mind the Gap: The State of Girls’ Education in Crisis and Conflict - Inter-agency Network for Education in Emergencies (INEE, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:DWS86NS8 2405685:54KVWNVR

Distance Learning during COVID-19 - Inter-Agency Network for Education in Emergencies (2020)
The third webinar of the INEE COVID-19 webinar series focused on providing distance learning in low-resource and low tech environments. The webinar highlighted the challenges currently facing EiE practitioners in the face of the school closures and restricted movement associated with COVID-19. EiE actors shared guidance and recommendations for continuing learning along with practical examples. More information about this webinar and INEE's COVID-19 response can be found on the INEE website: https://inee.org/collections/coronavi...
KerkoCite.ItemAlsoKnownAs: 2339240:H4HXTLS5 2405685:M9VJIUJC

A Guidance Note for Teacher Wellbeing in Emergency Settings - Inter-agency Network for Education in Emergencies (INEE, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:IP6AGVVP 2405685:MUMW9BCS

Teacher Wellbeing Resources Mapping & Gap Analysis - Inter-Agency Network for Education in Emergencies (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:8AFTF3MZ 2405685:X759APEH

Promising Practices in Teacher Professional Development - Inter-Agency Network for Education in Emergencies (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:74VNBZDB 2405685:GI2TV5HH

Education technology | INEE - Inter-Agency Network for Education in Emergencies
KerkoCite.ItemAlsoKnownAs: 2339240:CUHU5S82 2405685:JEK9AEX4
Keywords: ⛔ No INSPIRE recid found

Minimum Standards Handbook - Inter-Agency Network for Education in Emergencies (2012)
KerkoCite.ItemAlsoKnownAs: 2339240:36HRNX48 2405685:9DU2357U

Minimum Standards for Education: Preparedness, Response, Recovery - Inter-Agency Network for Education in Emergencies (Inter-agency Network for Education in Emergencies (INEE), 2010)
The Handbook is designed to give governments and humanitarian workers the tools that they need to address both local and global goals. It is the first step toward ensuring that education initiatives in emergency situations provide a solid and sound basis for post-conflict and disaster reconstruction. The INEE Minimum Standards express a commitment that all individuals – children, youth, and adults – have a right to education during emergencies and fragile contexts. They echo the core beliefs of the Sphere Project: that all possible steps should be taken to alleviate human suffering arising out of calamity and conflict, and that people affected by disaster have a right to life with dignity.
KerkoCite.ItemAlsoKnownAs: 2339240:FAJ3UVBG 2405685:WGWD3QAP

Landscape Review: Education in Conflict and Crisis - How Can Technology Make a Difference? - Inter-agency Network for Education in Emergencies (INEE). (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:4LDJAPYI 2405685:TS3U5UDR 4803016:HC52EFPN

EiE Glossary: Education in Emergencies - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:6N75ASRS 2339240:SQ3FSFGV 2405685:AILTYPCA 2405685:TE7LWUX7

Disability-Inclusive EiE Resources Mapping and Gap Analysis - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:M3KFL76D

Disability-Inclusive Education in Emergencies: Key concepts, approaches, and principles for practice - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:LXTVX8S5

Distance Education in Emergencies - Inter-agency Network for Education in Emergencies (INEE) (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:WJF8UCSK 2405685:VBJPL58M

Refugee education during COVID-19: Crisis and Opportunity - Inter-Agency Network for Education in Emergencies (INEE) (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:A3ZURZSV 2405685:KPBE2DZ3

Coronavirus (COVID-19) Resources | INEE - Inter-agency Network for Education in Emergencies (INEE). (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:NH7Z3RSH 2405685:HHMLYB2R 4803016:PT2WIUFL

Rapid Evidence Summary on Mass Communication | - Inter-agency Network for Education in Emergencies (INEE). (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:4UN5C9R9 2405685:49VB9WVT 4803016:7IPJKW8J

Technical Note: Education during the COVID-19 Pandemic. - Inter-agency Network for Education in Emergencies (INEE). (2020)
We are thrilled to share a new INEE Technical Note on Education during the COVID-19 Pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:G7EH66SF 2405685:H32K3JQ5 4803016:LPDQQ8PI

Minimum Standards for Education: Preparedness, Response, Recovery - Inter-agency Network for Education in Emergencies (INEE) (2024)
KerkoCite.ItemAlsoKnownAs: 2339240:CVK7GGEM 2339240:Y8G3HN56 2405685:E88FW6A5 2405685:Q5LVCBEJ

Checklist for Information and Communications Technologies (ICT) Interventions to Support Education in Crisis and Conflict Settings - Inter-agency Network for Education in Emergencies (INEE); USAID (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:NVCE2ZNU 2405685:ULHX8AES

Accelerated Education in the Democratic Republic of Congo, South Sudan, Tanzania and Uganda - Accelerated Education Working Group (AEWG); Inter Agency Network for Education in Emergencies (INEE) (2022)
KerkoCite.ItemAlsoKnownAs: 2405685:FNIQVHQ6